STUDY OF DIVERSITY OF BUBARA FISH (Carangidae) IN WAEHERU BEACH AMBON ISLAND - Ririhena, Manias; Lapu, Petrus; Wakano, Deli (RUMPHIUS, 2020)
Waiheru coastal waters are a coastal area that has diverse ecosystems (mangrove forests, seagrass beds, and other marine biota), so that it has quite high potential for coastal and marine resources (both fish and non-fish). The potential of trevally fish resources in Indonesian waters needs to be known so that it can be developed as an asset in marine tourism activities. The trevally fish is a type of surface (pelagic) fish. This fish is very popular with the community and lives in shallow coastal waters, corals and rocks. The aim of this study was to determine the diversity of trevally fish in the coastal waters of Waeheru, the inner part of Ambon Bay. The research was conducted in August 2013. Sample identification was carried out at UPT Laboratory, Ambon Marine Biota Conservation Center. Observational type research is by making direct observations in the field. Sampling stations consist of 3 stations, repeated 3 times at each station. From the results of the study obtained 11 species of Bubara fish (Carangidae) and 66 individuals. The highest diversity index value was found at station II, namely, 941 and the lowest was found at station III, namely 1,435. The diversity of fish species that is more commonly found is the Caranx Sexfasciatus fish which can be found at each station. The results of water quality measurements in the coastal waters of Waeheru still show a good range for fish life in these waters.